Steady as She Goes-Estimating Potential Output During Financial 'Booms and Busts' - Berger, Helge (IMF Working Papers; Working Paper ;, 2015)
Potential output-in the sense of the GDP level or path an economy can sustain over the medium term-is a crucial benchmark for policymakers. However, it is difficult to estimate when financial 'booms and busts' are driving the real economy. This paper uses a simple multivariate filtering approach to illustrate the role financial variables play in driving potential or sustainable output. The results suggest that it moves more steadily during financial 'boom and bust' periods than implied by conventional HP filter estimates, which tend to more closely follow actual GDP. A two-region, multisector New Keynesian DSGE model with financial frictions sheds light on the economic forces that could be behind the results obtained from the filter. This has important implications for policymakers.